2009
DOI: 10.1002/ijc.24762
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D mediates its action in human colon carcinoma cells in a calcium‐sensing receptor‐dependent manner: downregulates malignant cell behavior and the expression of thymidylate synthase and survivin and promotes cellular sensitivity to 5‐FU

Abstract: Vitamin D (VD) protects against colon carcinogenesis by mechanisms not fully understood. We had earlier reported on the similarity in the biologic action of VD and that of the calcium-sensing receptor (CaSR) in human colon carcinoma cells. At the molecular level, the CaSR gene contains 2 VD response elements and VD stimulates the expression of CaSR. In this study, we investigated on the relationship between VD action and CaSR function. We determined and compared the action of VD in human colon carcinoma cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
72
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 29 publications
0
72
0
Order By: Relevance
“…Calcipotriol and lentinan promote chemosensitivity in a CaSRdependent manner. As we have recently reported, CaSR is required in mediating calcitriol-promoted chemosencitivity in human colon carcinoma cells (12). We hypothesized that the same mechanism governed the effects of calcipotriol and lentinan.…”
Section: Calcipotriol and Lentinan Induce Casr Expressionmentioning
confidence: 80%
See 3 more Smart Citations
“…Calcipotriol and lentinan promote chemosensitivity in a CaSRdependent manner. As we have recently reported, CaSR is required in mediating calcitriol-promoted chemosencitivity in human colon carcinoma cells (12). We hypothesized that the same mechanism governed the effects of calcipotriol and lentinan.…”
Section: Calcipotriol and Lentinan Induce Casr Expressionmentioning
confidence: 80%
“…We have recently reported that induction of CaSR in human colon carcinoma cells by calcitriol promoted the sensitivity of the cells to the anticancer drug 5-FU (12). Since calcipotriol and lentinan exhibited similar effects in inducing CaSR expression as calcitriol, we hypothesized that these compounds may also be able to strengthen chemosensitivity in human colon carcinoma cells.…”
Section: Calcipotriol and Lentinan Induce Casr Expressionmentioning
confidence: 97%
See 2 more Smart Citations
“…15 Moreover, it has been reported that vitamin D mediates its action in human colorectal cancer cells in a CASR-dependent manner and downregulates malignant cell behavior. 21 Ion transport systems are often altered in human cancer. Downregulation of CASR protein expression has been reported in colorectal cancer tissues.…”
mentioning
confidence: 99%